Therapeutic hypothermia and cardiac intervention after cardiac arrest in pregnancy with underlying maternal arrhythmia: A case report - James P. Hogg, III; Lorene Atkins Temming; Rebecca Pollack (Elsevier, 2020)
There are few case reports of utilization of therapeutic hypothermia during pregnancy, and most report successful maternal and fetal outcomes. There is no available evidence that supports withholding therapeutic hypothermia in these patients. There are no long-term data on neonatal outcomes. We report the case of a 28-year-old pregnant patient with long QT syndrome who experienced multiple cardiac arrests during the second trimester and underwent therapeutic hypothermia, cardiac ablation, transvenous pacemaker placement, and placement of an implantable cardioverter defibrillator (ICD). She subsequently delivered a viable infant at term. The evidence seems to support the use of hypothermia during pregnancy, but patients should be counseled about the unknown maternal and fetal risks and long-term neonatal outcomes. Decisions to utilize therapeutic hypothermia should be made on an individual basis.